About distance as a problem - Baltar, Rosalía (Universidad Nacional del Litoral, 2021)
In this dossier we set out to bring together a series of works that analyze, revise, and update the notion of distance, a central concept for literary theory. From the Russian formalism this concept returns in more current theories and in contemporary literature. The distance supposes a taking of position within the literature with respect to the approached object in which places of enunciation are defined, spaces and invisible subjectivities are enabled. Distance is a procedure that makes other glances and inscriptions on bodies work, and the recovery of vestiges of memory that problematize temporality. The distance can be a retreat or an extended field in continuous movement. Against the fixist notions, the geographical turn proposed another way of thinking, a cartography that is permanently reconfigured by founding other territories and decolonizing others. Literature insists on this exercise that it is a form of estrangement.